Determinan yang Berhubungan dengan Perilaku Kesehatan Reproduksi Pada Mahasiswa di Kota Padang - Nurul Rizyana; Afzahul Rahmi (Pelantar Press, 2025)
Risky sexual behavior among adolescents has become a global public health problem. Negative sexual behavior can cause a variety of long-term problematic consequences. In 2021, the Padang City Health Service found 19 new cases of AIDS (18 men and 1 woman. The number of HIV/AIDS cases according to age groups showed that the highest number of cases were in the 25-49 year age group, namely 162 cases and 20-24 year olds as many as The 56 cases in this age group fall into the sexually active productive age group, indicating that this group of people had previously had casual sex during their teenage years professionalism among students at campus , 56.1% of respondents had a positive attitude towards sexual behavior and reproductive health, and 50.6% had risky sexual behavior for reproductive health. There is a relationship between the level of knowledge p-value = 0.0001, attitude (p value = 0.001), peer influence (p-value = 0.038). To prevent risky sexual behavior in students, a comprehensive approach is needed, requiring collaboration between parents, teachers and peers, good communication between parents, students and positive peer influence. Campuses can increase knowledge about preventing risky sexual behavior in students